Valores Referenciais para Procedimentos Odontológicos (VRPO) em Ortodontia - Maruo, Ivan Toshio; Saga, Armando; Camargo, Elisa Souza; Guariza Filho, Odilon [UNESP]; Tanaka, Orlando; Maruo, Hiroshi (FapUNIFESP (SciELO), 2009)
Introduction: The cost of orthodontic treatment is a very important issue. The aim of this study was to analyze the current Indicative Values for Dental Procedures (IVDP) for orthodontic procedures. Methods: Laws, dental entities papers and scientific literature were utilized. Results: Laws are too general and only offer abstract parameters when define remunerations. Current IVDP vary in the same State, according to the consultant entity. Dental entities interpret that general clinicians can practice Corrective Orthodontics, but new scientific studies begin to question this understanding. The Brazilian Association of Orthodontics and Dentofacial Orthopedics (ABOR) suggests that IVDP for orthodontic specialty must be formulated. Conclusion: Current IVDP are not standardized and are below the correct values for orthodontic procedures, because they are the mean of general clinicians and orthodontists remunerations; and ABOR is legally and ethically supported to claim specific IVDP for orthodontic specialty.
Indicative Values for Dental Procedures (IVDP) in Orthodontics
Keywords: Health plans; IVDP; Remuneration